(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We performed a molecular theory to study the switching mechanism of mixed brushes. For mixed brushes, because of the different solvent selectivity, one species forms the poor solvent layers, whereas another species creates the upper, good solvent layer. The structural properties of the mixed brushes were analyzed in detail for various solvent responds. The thermodynamic properties of the mixed brushes, such as the lateral pressure-area isotherms and chemical potentials, are studied as a function of surface coverage. The possibility of perpendicular segregation in mixed brushes is explained. The presented results allow us to quantify the responsive features of mixed brushes and provide guidance for the design of multicomponent brushes for specific applications.